An In‐Depth Structural Study of the Carbon Dioxide Adsorption Process in the Porous Metal–Organic Frameworks CPO‐27‐M. Issue 8 (16th March 2017) - Pato‐Doldán, Breogán; Rosnes, Mali H.; Dietzel, Pascal D. C.
Abstract: The CO2 adsorption process in the family of porous metal–organic framework materials CPO‐27‐M (M=Mg, Mn, Co, Ni, Cu, and Zn) was studied by variable‐temperature powder synchrotron X‐ray diffraction under isobaric conditions. The Rietveld analysis of the data provided a time‐lapse view of the adsorption process on CPO‐27‐M. The results confirm the temperature‐dependent order of occupation of the three adsorption sites in the pores of the CPO‐27‐M materials. In CPO‐27‐M (M=Mg, Mn, Co, Ni, and Zn), the adsorption sites are occupied in sequential order, primarily because of the high affinity of CO2 for the open metal sites. CPO‐27‐Cu deviates from this stepwise mechanism, and the adsorption sites at the metal cation and the second site are occupied in parallel. The temperature dependence of the site occupancy of the individual CO2 adsorption sites derived from the diffraction data is reflected in the shape of the volumetric sorption isotherms. The fast kinetics and high reversibility observed in these experiments support the suitability of these materials for use in temperature‐ or pressure‐swing processes for carbon capture. Abstract : All about adsorption : A time‐lapse view of the CO2 adsorption process in the CPO‐27‐M family is obtained with the help of powder synchrotron X‐ray diffraction. The results provide insights into the host–guest structures of the CO2 molecules within the metal–organic frameworks on the molecular level and the temperature‐dependent order of occupation of the different adsorption sites in the pores.